Design and thermoeconomic analysis of a multi-effect desalination unit equipped with a cryogenic refrigeration system. (15th December 2019) - Ghorbani, Bahram; Shirmohammadi, Reza; Amidpour, Majid; Inzoli, Fabio; Rocco, Matteo
Highlights: Developing of a trigeneration system for fresh water & LNG production using hybrid refrigeration systems. Using solar dish collector for generating heat & power in the trigeneration system. Reduction in CO2 emission & natural gas consumption with the aid of solar dish collectors. Conducting exergy, sensitivity analyses & economic evaluation for the two integrated structures. Abstract: In this paper, a hybrid tri-generation system is designed to produce LNG and freshwater simultaneously based on a multi-effect desalination system and analyzed using energy and exergy analyses. For natural gas liquefaction, the initially required cooling of the cycle is supplied by ammonia-water absorption system, and the required intermediate cooling load and liquefaction process are provided by a refrigeration system with mixed fluid. Two alternatives for providing power generation to the system and the required heat for driving the absorption cycle have been considered and compared. The first alternative relies on a natural-gas-fired power plant, while the second is based on steam-solar power plant with dish collectors. The former results in the total energy efficiency of 85.8% (LHV). The highest thermodynamic irreversibilities occur in the heat exchangers (61%), even if they have the highest exergy efficiency compared to the other plant equipment. On the other hand, using solar dish collectors enables to decrease carbon dioxide emissions by 40%, and increases freshwater and LNG production by 95% and 4.7% respectively. The power obtained per kg of LNG produced is about 0.19 kWh, which is less than or equal to the other similar patents. The results of the economic analysis with the annualized cost method of the system show that the products prime cost of both structures 1 and 2 are equal to 0.2580 and 0.1784 US per kg of LNG, respectively. A suitable strategy for modelling enhancement of system's parameters is suggested by expanding of sensitivity analysis on the important parameters of the developed system.